PRODUCTION OF SYNTHESIS GAS BY CATALYTIC HYDROCARBON CONVERSION - Akhmedov Islombek; Umarov Isroil; F.Kodirova (Journal of new century innovations, 2023)
Abstract: The paper presents the main points of producing synthesis gas from a wide range of hydrocarbons of various origins. Technological options for producing synthesis gas from hydrocarbon mixtures are proposed.